Only by Knowing The Other Shalt Thou Know Thyself: Americanness and Britishness as Defining Forces for Canadianness in Hugh MacLennan’s Early Novels - Maxmilian Rhys (Acta Universitatis Sapientiae: Philologica, 2024)
In the aftermath of World War II, Canada stood at a crossroads marked by mutual incomprehension and a lack of willingness to understand The Other on the part of both Anglo- and Franco-Canadians. At that time, its identity was only in the process of forming itself into a prospective national conscience. Hugh MacLennan was one of the few writers of that period to try to understand the full depths and intricacies of the historical burden characterizing the difficult coexistence of the two “Founding Nations.” In his specific, personal way, MacLennan tried to show and prove that these national, linguistic, social, as well as religious barriers should be finally abandoned as a matter of the past. Communicating his sympathies and understanding for the French-speaking “minority” within the whole of Canada through his novels may seem to be, yet is not, his primary goal. Another significant objective of his frequently didactic novels was to show the undeniably influential role of Britishness and Americanness in the process of “defining Canada’s Canadianness.” This issue was even more important than attempting to solve the endless, insoluble skirmishes between the English and French Canadians. Not only were the striking differences between Canadians, and Americans and the British a way to help define Canadianness, but the encounter(s) with The Other on the outside presented a potential prospect of solidifying and strengthening the “internal Canadian bond,” with MacLennan’s oeuvre contributing to the very definition of the modern Canadian nation’s identity. Taking into account views related to the post-colonial theories, the article (re)confirms the position of MacLennan aspiring to be the nation’s first true post-colonial (or non-colonial) writer.